Odpowiedź :
Odpowiedź:
a) 18 + (-21) = 18 - 21 = -(-18 + 21) = -(21 - 18) = -3
b) 24 + (-51) = 24 - 51 = -(-24 + 51) = -(51 - 24) = -27
c) 27 - (-9) = 27 + 9 = 36
d) -60 - (-17) = -60 + 17 = -(60 - 17) = -43
e) -7 + (-2) = -7 - 2 = -(7 + 2) = -9
f) -29 + (-28) = -29 - 28 = -(29 + 28) = -57
g) -6 + 0,5 = -(6 - 0,5) = -5,5
h) 10 + (-2,5) = 10 - 2,5 = 10 - 2 - 0,5 = 8 - 0,5 = 7,5
i) 0,1 - 1 = -(-0,1 + 1) = -(1 - 0,1) = -0,9
j) -8 - 2,5 = -(8 + 2,5) = -10,5
k) -3 1/3 - (-3) = -3 1/3 + 3 = 3 - 3 1/3 = 3 - 3 - 1/3 = -1/3
l) -8 - (- 1 1/4) = -8 + 1 1/4 = -(8 - 1 1/4) = -(8 - 1 - 1/4) = -(7 - 1/4) = -6 3/4
m) -5,4 - (-12) = -5,4 + 12 = 12 - 5,4 = 12 - 5 - 0,4 = 7 - 0,4 = 6,6
n) 28 - 70 1/3 = -(-28 + 70 1/3) = -(70 1/3 - 28) = -42 1/3
o) -17 1/4 + 15 = -(17 1/4 - 15) = -2 1/4
p) -73 + 13,3 = -(73 - 13,3) = -(73 - 13 - 0,3) = -(60 - 0,3) = -59,7
q) -48 1/7 - (-13) = -48 1/7 + 13 = -(48 1/7 - 13) = -35 1/7
r) -80,8 - (-29) = -80,8 + 29 = -(80,8 - 29) = -51,8